Process Parameters Optimization of Potential SO42-/ZnO Acid Catalyst for Heterogeneous Transesterification of Vegetable Oil to Biodiesel - Istadi Istadi; Didi D. Anggoro; Luqman Buchori; Inshani Utami; Roikhatus Solikhah (Bulletin of Chemical Reaction Engineering & Catalysis, 2012)
Among the possible renewable energy resources, diesel fuels derived from triglycerides of vegetable oils and animal fats have shown potential as substitutes for petroleum-based diesel fuels. The biodiesel could be produced from vegetable oils over homogeneous catalyst, heterogeneous catalyst, or enzymatic catalyst. In this study, the synthesized SO42-/ZnO catalyst was explored to be used in the heterogeneous biodiesel production by using the vegetable oils and methanol. The study began with the preparation of SO42-/ZnO catalyst followed by the transesterification reaction between vegetable oil with methanol. The independent variables (reaction time and the weight ratio of catalyst/oil) were optimized to obtain the optimum biodiesel (fatty acid methyl ester) yield. The results of this study showed that the acid catalyst SO42-/ZnO was potential to be used as catalyst for biodiesel production through heterogeneous transesterification of vegetable oils. Optimum operating condition for this catalytic reaction was the weight ratio of catalyst/oil of 8:1 and reaction time of 2.6 h with respect to 75.5% yield of methyl ester products. The biodiesel product was also characterized to identify the respected fatty acid methyl ester components. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0) (Selected Paper from International Conference on Chemical and Material Engineering (ICCME) 2012)